DISTRIBUSI PENYAKIT DIARE DAN DETERMINAN DENGAN PEMETAAN WILAYAH PROVINSI JAWA BARAT TAHUN 2020 - Husna, Safira Alifia; Soviadi, Nabila Vebiana (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2024)
Diarrhea is a symptom of infection in the intestinal tract which can be caused by various bacterial, virus and parasitic organisms. The morbidity rate of toddler’s diarrhea in Indonesia in 2020 is 843/1000 population and the mortality rate has continued to increase since 2019. Main factors related to the spread of diarrheal disease are environmental and behavioral factors including population density, drinking water facilities and household waste. This study used a descriptive design to obtain an overview regarding the mapping of the distribution and classification of diarrheal diseases. The results of diarrheal disease research were classified into very low, low, medium, high and very high. From the mapping it can be concluded that there are other factors apart from population density, access to drinking water facilities and households with healthy lifestyle behavior that allow cases of diarrhea to occur.